Improving Fruit and Vegetable Consumption in Elementary School Students: A Systematic Review of Interventions - Hashemi, Seyedeh Zeinab; Hazavehei, Seyed Mohammad Mehdi; Shahabadi, Sara (International Journal of Child Health and Nutrition, 2013)
<!– [if gte mso 9]> 800x600 <![endif]–> Introduction: Less than 15% of the 4 to 8-year old children consume the recommended servings of fruit and vegetables (FV). Early years of life play an important role in establishing healthy eating habits. School is an appropriate setting for healthy eating habits interventions. The purpose of this systematic review is evaluation of school-based interventions to improve FV consumption in elementary school students. Methods: In this systematic review, we performed a search in several databases such as PubMed, Web of Science, Education Resources Information Center (ERIC), Science Direct and Google Scholar. Studies published between January 2005 and December 2012 were included. In examining the studies, we focused on design, strategies and outcomes of the interventions. Results: Eleven studies met the inclusion criteria. Interventions in these three classifications (gardening and education, educational programs and providing FV) have positive effects on children’s FV intake. Multi-component education is more effective than other cases in children willingness for FV consumption. Gardening strategies: participating in hands-on gardening experiences, engaging in gardening challenges and preparing a party by student’s garden products. Educational strategies: nutrition education classes, electronic learning by using the popular cartoon characters and child actors as symbolic role models and strategies to improve family awareness like series of newsletters for parents and homework tasks for parents and children. Providing strategies: providing fee-based or free FV at school. Conclusion: Long-term multi-component (gardening, education and providing FV) interventions with the application of behavioral change theories and models are effective to reach the expected results. <!–[endif] –>